2016
DOI: 10.1007/s13361-016-1395-z
|View full text |Cite
|
Sign up to set email alerts
|

Difference of Electron Capture and Transfer Dissociation Mass Spectrometry on Ni2+-, Cu2+-, and Zn2+-Polyhistidine Complexes in the Absence of Remote Protons

Abstract: Abstract. Electron capture dissociation (ECD) and electron transfer dissociation (ETD) in metal-peptide complexes are dependent on the metal cation in the complex. The divalent transition metals Ni 2+ , Cu 2+ , and Zn 2+ were used as charge carriers to produce metal-polyhistidine complexes in the absence of remote protons, since these metal cations strongly bind to neutral histidine residues in peptides. In the case of the ECD and ETD of Cu 2+ -polyhistidine complexes, the metal cation in the complex was reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Because the binding energy between (Cu2L1) 3+ and T18p was decreased by reduction of Cu 2+ in the complex, (CuL1) + and [T18p + Cu] + would be formed by ETD-MS/MS. This result is good agreement with previously reported ETD-MS/MS of Cu 2+ -peptide complex30 and the presence of Cu 2+ in the precursor ion suppress the N-Cα bond cleavage by ETD-MS/MS.Regarding the Figure4d, ETD of [Ga2L2 + (T18p -2H)] 3+ selectively induced C6H6N• losses, leading to the [Ga2L2 + (T18p -2H -C6H6N)] 2+ and [Ga2L2 + (T18p -2H -2C6H6N)] + . The C6H6N• loss was induced the electron association to the pyridine ring in the complex, and the N-Cα bond cleavage is completely suppressed by the presence of (Ga2L2) 5+ in the precursor.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…Because the binding energy between (Cu2L1) 3+ and T18p was decreased by reduction of Cu 2+ in the complex, (CuL1) + and [T18p + Cu] + would be formed by ETD-MS/MS. This result is good agreement with previously reported ETD-MS/MS of Cu 2+ -peptide complex30 and the presence of Cu 2+ in the precursor ion suppress the N-Cα bond cleavage by ETD-MS/MS.Regarding the Figure4d, ETD of [Ga2L2 + (T18p -2H)] 3+ selectively induced C6H6N• losses, leading to the [Ga2L2 + (T18p -2H -C6H6N)] 2+ and [Ga2L2 + (T18p -2H -2C6H6N)] + . The C6H6N• loss was induced the electron association to the pyridine ring in the complex, and the N-Cα bond cleavage is completely suppressed by the presence of (Ga2L2) 5+ in the precursor.…”
supporting
confidence: 93%
“…However, the yield of metal-peptide complex is usually low when the free metal cation was used. [21][22]30 To increase the yield of metal-phosphopeptide complex, we have recently used a dinuclear zinc complex, (Zn2L1) 3+ (L1 = alkoxide form of 1,3-bis[bis(pyridin-2-ylmethyl)amino]propan-2-ol), also known as the phosphate capture molecule "phos-tag", [32][33][34] as an ionizing reagent. 16 The molecular structure of (Zn2L1) 3+ is shown in Scheme 1a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that in the case of this His-rich peptide, complexation with Zn 2+ had a considerable negative impact on overall fragmentation efficiency. In the light of literature findings showing that positively charged, non-redox-active ions support or enhance fragmentation 81 86 , we suggest that this inefficient cleavage for the Zn 2+ complex has structural origins ( vide infra ).…”
Section: Resultsmentioning
confidence: 71%
“… 115 Further, both ECD and ETD of 2+ ions of histidine peptides that lacked both amino groups and acidic sites (acetylation of the N-terminal amine and amidation of the C-terminal carboxylate), with Zn 2+ (∼8.6 eV), Ni 2+ (∼10.5 eV), or Cu 2+ (∼12.6 eV) attached, produced only a and b but no c , z ˙ or c ˙, z fragments. 116 In an ETD study of 15 different peptides, Vachet and Dong observed c and z ˙ fragments with Cu 2+ instead of Cu + attached, consistent with electron transfer to protonated sites instead of Cu 2+ . Moreover, they found a positive correlation between the number of residues that strongly bind Cu 2+ ( i.e.…”
Section: Resultsmentioning
confidence: 91%